Antioxidant Activities of Chloroform and Aqueous Fractions of Myrmecodia Pendenss Extract: A Preliminary Study - Yohanes Buang; Ermelinda Noya; Pius D. Ola; Theo Da Cunha (Journal of Applied Chemical Science, 2013)
There have been elucidated the antioxidant activities of chloroform and aqueous fractions of methanol extracts isolated from myrmecodia pendenss. The study was firstly started by maceration of myrmecodia pendenss powder in certain quantity of pure methanol solvent and followed by gradual partition of the methanol extract with chloroform and distillated water and then purified with column chromatography. The chemical contents migrated into both those later solvents were detected by GC-MS and their functional groups were detected by FT-IR instruments. Thereafter, the antioxidant activities of the migrated compounds in each those solvents were determined using hydrogen peroxide protocol and the absorbance was measured at 240 nm. The ascorbic acid solution was used as control. The results showed that FT-IR spectrum showed methylene and ethene groups are existed within the compounds contained by the extracts as well as the hydroxyl, carbonyl, aromatic, and keton groups. Furthermore, the GC-MS spectrum indicated the compounds that are existed within the chloroform and the aqueous fractions of the extract. The average absorbances of compounds contained within the chloroform and aqueous fractions were 0.161 and 0.112, respectively, whereas that of the control was 0.085. Those absorbance data conclusively indicated that higher absorbance higher residue of chromophore content existed within the fraction and higher failures of hydroxylation reactions. It was however, the antioxidant activities of the aqueous fractions were higher than those of the chloroform fractions.